New chromium(III) complexes as highly active catalysts for olefin polymerization - Enders, Markus; Fernández, Pablo; Ludwig, Gunter; Pritzkow, Hans (Organometallics, 2001)
Cyclopentadienyl ligands functionalized by quinoline or N,N-dimethylaniline have an ideal and rigid geometry for the formation of half-sandwich compounds. As a result, stable chromium(III) complexes 5-8 with intramolecular nitrogen coordination have been obtained. Treatment with MAO leads to highly active, temperature-stable catalysts for the polymerization of ethylene.